Seafood Labelling: Awareness and Perception Among Consumers of Organized Fish Retail Outlets in India - Mugaonkar, Pankajkumar Hanmantrao; Kumar, Nalini Ranjan; Krishnan, M. (Indian Journal of Marketing, 2013)
The study investigates the awareness and perception about seafood labelling among seafood consumers in India, and also provides insights into 'what exactly do consumers seek from seafood labels?' This indirectly revealed the consumers' knowledge about seafood labelling. In total, 120 consumers were interviewed in organized retail stores in Pune during July - October 2012. Importance of seafood labelling leads to better buying, better and balanced nutrition, ensuring only good-quality products are purchased by the consumers, and consumers are not deceived into purchasing sub-standard products. It was found that 92.5% of the consumers were aware of seafood labelling. Likert scale was used to rank the importance accorded to the details given on the labels of seafood products by consumers. The true nature of the product was ranked as the most important detail on the label by 100% of the respondents followed by the name of the fish/product by 97.5% of the respondents, and nutritional information was rated as the most important detail by 96.67% of the respondents. Origin of the fish/seafood products was given the lowest ratings by 38.33% of the consumers. Furthermore, it was found that 69% of the consumers always read the seafood labels, whereas 7.5% of the consumers never read the same. Maximum likelihood estimates revealed that though the educational level of the respondents was the most important determinant of frequency of reading seafood labels, it showed a negative effect. Marginal effects of increase in income indicated an increase in likelihood of reading seafood labels more frequently; that is, always. The marginal effects in case of family size and awareness were the same. 95% of the respondents never came across any 'mislabeled seafood,' and 75% of the respondents demanded common seafood certification labels. To conclude, there is a dearth of awareness regarding seafood labelling in our country, and consumers need to be better informed about seafood labelling, its importance, and certifications. This will ensure that only good quality products are purchased by the customers.